Rapid detection of specific proteins expressed in cytoplasmic male-sterile line of tuber mustard using SDS-PAGE - ZHANG Ming-fang; CHEN Li-ping; HIRATA Yutaka; CAO Jia-shu; CHEN Zhu-jun (浙江大学学报. 农业与生命科学版)
In this paper, two specific proteins with molecular weights of ca. 14.4 kD and 13.0 kD were detected by SDS-PAGE in floral organs of CMS line of tuber mustard, of which the 14.4 kD protein was clearly over-expressed. Nevertheless, no difference was detectable in banding patterns of soluble proteins of leaves and roots between CMS and male fertile lines during both vegetative and reproductive stages. It is suggested that the expression of specific proteins is quite organ-specific and over-expression of the 14.4 kD protein may be responsible for CMS of tuber mustard.